2020
DOI: 10.1093/ijnp/pyaa058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Exposure to Low-Dose delta-9-Tetrahydrocannabinol in Adolescence and Adulthood on Serotonin/Norepinephrine Neurotransmission and Emotional Behavior

Abstract: Background Chronic exposure to the Δ9-tetrahydrocannabinol (THC), the main cannabis pharmacological component, during adolescence has been shown to be associated with an increased risk of depression and suicidality in humans. Aims Little is known about the impact of the long-term effects of chronic exposure to low doses of THC in adolescent compared to adult rodents. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Additionally, chronic exposure to THC in adolescent mice increased the percentage of shredding in the nestlet shredding task [ 118 ] and immobility times in adult rats during the forced swim test [ 119 ]. More recently, a study by De Gregorio et al (2020) showed that chronic exposure to low-dose THC in adolescent rats leads to persistent behavioral abnormalities related to some but not all aspects of depressive reactivity [ 120 ]. In particular, THC administration in rats induced some anxiety behaviors (fewer entries into the open arms of the elevated plus maze) and altered serotoninergic neuron firing rate activity [ 120 ].…”
Section: Effect Of Cannabinoids On Behavioral Processes: Stress Anxiety Learning and Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, chronic exposure to THC in adolescent mice increased the percentage of shredding in the nestlet shredding task [ 118 ] and immobility times in adult rats during the forced swim test [ 119 ]. More recently, a study by De Gregorio et al (2020) showed that chronic exposure to low-dose THC in adolescent rats leads to persistent behavioral abnormalities related to some but not all aspects of depressive reactivity [ 120 ]. In particular, THC administration in rats induced some anxiety behaviors (fewer entries into the open arms of the elevated plus maze) and altered serotoninergic neuron firing rate activity [ 120 ].…”
Section: Effect Of Cannabinoids On Behavioral Processes: Stress Anxiety Learning and Memorymentioning
confidence: 99%
“…More recently, a study by De Gregorio et al (2020) showed that chronic exposure to low-dose THC in adolescent rats leads to persistent behavioral abnormalities related to some but not all aspects of depressive reactivity [ 120 ]. In particular, THC administration in rats induced some anxiety behaviors (fewer entries into the open arms of the elevated plus maze) and altered serotoninergic neuron firing rate activity [ 120 ]. In another study, it was shown that rats treated with chronic THC during adolescence showed a higher level of anxiety-like behaviors, which led to a significant reduction in food intake and body weight [ 121 ].…”
Section: Effect Of Cannabinoids On Behavioral Processes: Stress Anxiety Learning and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Widely used worldwide, cannabinoids have attracted much attention for their potential role in health and disease, especially in psychiatry (2). Translational research has significantly advanced our understanding of the neuropsychiatric effects of cannabinoids (3)(4)(5)(6). Adopting a translational perspective, the Research Topic presented here brings together up-to-date knowledge of these fascinating and complex chemical substances and how they may modulate mental health.…”
Section: Editorial On the Research Topic The Endocannabinoid System: Filling The Translational Gap Between Neuroscience And Psychiatrymentioning
confidence: 99%
“…6,7 One of the main hypotheses for psychotic disorders implicates different types of cannabis and a dysregulation (aberrant endogenous signalling) between the two main psychoactive components Δ-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). 6,7 Furthermore, THC and CBD might differently interfere with the endocannabinoid and other neurotransmitter systems, 9,10 and hence, both substances have different acute-, residual-and long-term effects on affective, cognitive and sensorimotor functioning. 11 On one side, THC can acutely increase positive mood 12 and reduce anxiety at low doses.…”
Section: Introductionmentioning
confidence: 99%